Telemedicine, COVID-19, and disparities: Policy implications. Issue 3 (September 2020) - Ortega, Gezzer; Rodriguez, Jorge A.; Maurer, Lydia R.; Witt, Emily E.; Perez, Numa; Reich, Amanda; Bates, David W.
Highlights: COVID-19 has resulted in a dramatic increase in the use of telemedicine but this could worsen disparities. We review recent telemedicine policy changes and their implications regarding disparities. We also discuss what systems can do to improve access to telemedicine and to best meet the needs of underserved patients. Abstract: While the rapid expansion of telemedicine in response to the COVID-19 pandemic highlights the impressive ability of health systems to adapt quickly to new complexities, it also raises important concerns about how to implement these novel modalities equitably. As the healthcare system becomes increasingly virtual, it risks widening disparities among marginalized populations who have worse health outcomes at baseline and limited access to the resources necessary for the effective use of telemedicine. In this article, we review recent policy changes and outline important recommendations that governments and health care systems can adopt to improve access to telemedicine and to tailor the use of these technologies to best meet the needs of underserved patients. We suggest that by making health equity integral to the implementation of telemedicine now, it will help to ensure that all can benefit from its use going forward and that this will be increasingly integral to care delivery.